Between Preservation and Exploitation : Transnational Advocacy Networks and Conservation in Developing Countries - Fuentes-George, Kemi (Book collections on Project MUSE., 2016)
"In the late 2000s, ordinary citizens in Jamaica and Mexico demanded that government put a stop to lucrative but environmentally harmful economic development activities -- bauxite mining in Jamaica and large-scale tourism and overfishing on the eastern coast of the Yucatán Peninsula. In each case, the catalyst for the campaign was information gathered and disseminated by transnational advocacy networks (TANs) of researchers, academics, and activists. Both campaigns were successful despite opposition from industry supporters. Meanwhile, simultaneous campaigns to manage land in another part of the Yucatán and to conserve migratory birds in Egypt had far less success. Fuentes-George uses these four cases to analyze factors that determine the success or failure of efforts by TANs to persuade policymakers and private sector actors in developing countries to change environmental behavior."--Provided by publisher